PENGEMBANGAN HANDOUT BIOLOGI SMA BERBASIS KONTEKSTUAL DISERTAI GAMBAR BERWARNA PADA MATERI SISTEM EKSKRESI MANUSIA - Oktaviani, Arci; ARDI, ARDI; Amri, Erismar (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Excretion system is one of the topics in biology which requires the students to be able to make a linkage between the learning materials and the real world. Therefore, the teachers need to design a handout. This research was intended to produce a contextual-based handout accompanied with colorful pictures for teaching Human Excretion System. This was a developmental research which used 4-D models that consisted of four phases including defining, designing, developing and disseminating. The data gotten was analyzed by using percentage technique and interpreted descriptively. The result of the validation test indicated that the handout developed was valid in which the validity score was 89,55%. The handout was also practical. The practicality of the product could be seen from the score given by the teachers which was 91,15% and the score given by the students which was 83,62%. Therefore, it was concluded that the contextual-based handout accompanied with colorful pictures developed for teaching Human Excretion System had been valid and practicalÂ